Smartphone screen time and suicide risk in daily life captured through high-resolution screenshot data - Ross Jacobucci; Miguel Blacutt; Nilàm Ram; Brooke A. Ammerman (npj Digital Medicine)
Abstract Suicide rates are rising in the U.S., prompting interest in contributing factors like smartphone use. While screen time has been linked to mental health, its role in suicide risk is unclear. This study examined bidirectional associations between smartphone screen time and suicide risk in 79 adults with recent suicidal thoughts or behaviors. Over 28 days, participants provided ecological momentary assessments (EMA) of suicide risk six times daily and contributed ~7.5 million screenshots, collected every 5 seconds during phone use. Within-person increases in screen time were linked to elevated suicide risk in the following three hours, while screen time more than three hours prior predicted reduced planning and desire. Suicide risk also predicted subsequent screen time, and screen time was associated with greater EMA response rates. Findings suggest screen time may indicate both distress and coping, depending on context. These insights could inform real-time monitoring tools for suicide prevention and adaptive intervention strategies.